Mentor Minister launched UMP Cooperative - UMP, PNC
Domestic Trade, Cooperatives and Consumerism Minister and Universiti Malaysia Pahang (UMP) Mentor Minister Dato’ Sri Ismail Sabri Yaakob launched Koperasi UMP Berhad and UMP Coop Book Shop at the Chancellery Square, Gambang on March 10, 2012.